Nazwiska równe apelatywom na pograniczu polsko-ukraińskim – wybrane problemy - Czyżewski, Feliks (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The study presents selected appellative surnames taken from the List of the Alumni of the Wisznice High School in Southern Podlasie. The adopted criterion for selection was the rule that an appellative from which a surname was formed has to indicate – through its linguistic form or semantics – that it is a Ukrainism/Ruthenism. The analysis of the anthroponymic and lexicological material applies the method of comparative grammar, enriched with the dialectological method and complemented with the method of linguistic geography, with the analyzed surnames (Gładun/Gładuń, Haliburda, Hałaburda, Hładun, Hołod, Hołownia) juxtaposed with their corresponding anthroponyms in Poland and in Ukraine. The conclusions drawn from the analysis indicate that the surnames taken into consideration are anthroponyms typical of the Polish-Ukrainian/East Slavic borderland. One of the features of the linguistic borderland is the semantic variantivity of lexemes transferred onto the level of proper names. Another conclusion is that the surnames isolated during the analysis were formed from lexemes that have the status of peripheral archaisms.